Point-of-Care Ultrasound Abnormalities in Late-Onset Severe Preeclampsia: Prevalence and Association With Serum Albumin and Brain Natriuretic Peptide. Issue 1 (March 2020) - Ortner, C.M.; Krishnamoorthy, V.; Neethling, E.; Flint, M.; Swanevelder, J.L.; Lombard, C.; Fawcus, S.; Dyer, R.A.
Abstract : ( Anesth Analg . 2019;128(6):1208–1216) Care providers frequently use point-of-care ultrasound (POCUS) on pregnant women diagnosed with preeclampsia to prevent serious afflictions such as cerebral complications or cardiorespiratory failure. Present-day ultrasound research has found a number of indicators for pulmonary interstitial syndrome (PIS) and a higher optic nerve sheath diameter (ONSD), the latter of which could indicate elevated intracranial pressure. As of now, irregular laboratory markers of oncotic pressure and cardiac dysfunction have inconclusive clinical applications; many experts posit that reduced serum albumin level is a contributor to excessive brain fluid and brain swelling. These investigators examined patients with preeclampsia to determine how PIS, ONSD, brain natriuretic peptide (BNP), and serum albumin level contribute to cardiac dysfunction. They also aimed to study the comparison of information acquired from a POCUS examination to information recorded with traditional clinical methods.